UPAYA PEMERINTAH TIONGKOK MENCAPAI KEPENTINGAN EKONOMI DENGAN MENGESAMPINGKAN ISU EKSPLOITASI BURUH FOXCONN TAHUN 2010 – 2016 - Sembada, Crishna; Suwecawangsa, Adi Putra; Priadarsini, Ni Wayan Rainy (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2020): Hubungan Internasional Vol1, No1, th 2020, 2020)
ABSTRACT   This study aims to provide description about the Chinese Government's Efforts to Achieve Economic Interest by Leveraging the Foxconn Labor Exploitation Issue in 2010-2016. In the economic development in China, Deng Xiapoing issued an open door policy that caused foreign companies to enter, one of them and the biggest one was Foxconn. Foxconn entered China in 1988 and greatly influenced the economic development in China. But over time, Foxconn exploited his workers. China Labor Watch has a report on the exploitation and China still allows Foxconn to operate. China actually seeks to keep Foxconn investing. This research uses an explanative qualitative method with data collected through literature study. The conceptual framework used to examine the data is of national economic importance. This study found China's efforts in the form of subsidies, workers search assistance to tax cuts.   Keywords: China, Foxconn, Exploitation, National Economic Interest ABSTRACT   This study aims to provide description about the Chinese Government's Efforts to Achieve Economic Interest by Leveraging the Foxconn Labor Exploitation Issue in 2010-2016. In the economic development in China, Deng Xiapoing issued an open door policy that caused foreign companies to enter, one of them and the biggest one was Foxconn. Foxconn entered China in 1988 and greatly influenced the economic development in China. But over time, Foxconn exploited his workers. China Labor Watch has a report on the exploitation and China still allows Foxconn to operate. China actually seeks to keep Foxconn investing. This research uses an explanative qualitative method with data collected through literature study. The conceptual framework used to examine the data is of national economic importance. This study found China's efforts in the form of subsidies, workers search assistance to tax cuts.   Keywords: China, Foxconn, Exploitation, National Economic Interest